Geospatial technology for flood hazard mapping in the Adamawa State, Nigeria - Dahiru Mohammed Zakari, 1972-; Muhammad Zulkarnian Abd. Rahman, supervisor; Fakulti Geoinformasi dan Harta Tanah (2014)
Thesis (Sarjana Sains (Remote Sensing)) - Universiti Teknologi Malaysia, 2014